2017
DOI: 10.1002/jtr.2108
|View full text |Cite
|
Sign up to set email alerts
|

European outbound tourism in times of economic stagnation

Abstract: Accounting for the instability of tourism income elasticities in the European Union‐15 since 2004, estimations show that income elasticities in the period 2004–2014 were greater in slow‐growth periods (above 1) than in fast‐growth periods (below 1). Due to the gradual deterioration of the economic environment since 2004, the small income improvements in the fast‐growth periods were used relatively more for satisfying pent‐up demand for necessary consumer goods or precautionary savings than for traveling abroad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…Gunter and Smeral (2016), in reference to the structural changes observed frequently within the leisure sector, showed that structures changed in the long term and its positive impact on certain goods, such as international travel, slows down or disappears, also leading to a decline in income elasticities from period to period. Gunter and Smeral (2017) found that income elasticities were different in distinct growth periods between 2004 and 2014 for both the EU15 and EU28, showing how, on the one hand, in slow growth periods, the income elasticity had a value above 1 while, on the other hand, in the fast growth periods, the elasticity value was below 1. Additionally, the reaction of tourism demand to income changes could be asymmetric during different phases of the business cycle (Gunter and Smeral 2017; Smeral and Song 2013; Smeral 2018).…”
Section: Income and Tourism Demand: A Review Of Recent Literaturementioning
confidence: 97%
See 2 more Smart Citations
“…Gunter and Smeral (2016), in reference to the structural changes observed frequently within the leisure sector, showed that structures changed in the long term and its positive impact on certain goods, such as international travel, slows down or disappears, also leading to a decline in income elasticities from period to period. Gunter and Smeral (2017) found that income elasticities were different in distinct growth periods between 2004 and 2014 for both the EU15 and EU28, showing how, on the one hand, in slow growth periods, the income elasticity had a value above 1 while, on the other hand, in the fast growth periods, the elasticity value was below 1. Additionally, the reaction of tourism demand to income changes could be asymmetric during different phases of the business cycle (Gunter and Smeral 2017; Smeral and Song 2013; Smeral 2018).…”
Section: Income and Tourism Demand: A Review Of Recent Literaturementioning
confidence: 97%
“…Although studies of tourism demand modeling usually assume that income’s effect on tourism demand remains stable, irrespective of changes in the remaining factors, more recently an increasing body of literature has started to draw attention to the variability of the estimated income elasticity, striving to explain why the relationship between tourism and income can vary as a result of different factors. Empirical literature has identified various factors that could explain the variability of the income elasticity, such as financial and economic crises (Smeral 2009), the point in the business cycle (Smeral and Song 2013; Gunter and Smeral 2016), structural changes (Song, Witt, and Li 2009), different time periods (Gunter and Smeral 2016, 2017), different destination–origin pairs (Peng, Song, and Crouch 2014), and the income level at the destination country or continent (Martins, Gan, and Ferreira-Lopes 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this test for conventional structure change (that is, that is based on a classic regression model) has also been used quite frequently in tourism research [71][72][73][74][75], its use with logistic regression models and therefore, its contrast through a likelihood ratio test, is practically non-existent in the field of tourism research. Thus, this work presents a methodological novelty in the field of tourism research.…”
Section: Methodsmentioning
confidence: 99%
“…Gunter and Smeral (2016) compared the income elasticity of tourism demand in different world regions, finding that during the period between 2004 and 2013 it was lower than pre-viously because of the great recession between 2007 and 2009, financial crises, increasing unemployment, and insecurity; in fact, during the decade between 2004 and 2013, tourism goods became income inelastic with the coefficient varying from 0.20 in Southern Europe to 0.99 in Asia, reflecting the fact that tourism has become a necessity. Additionally, Gunter and Smeral (2017) investigated income elasticity across the business cycle, dividing it into fast growth-periods (expansion, peak and slowdown) and slow growthperiods (recession, through and recovery), revealing that between 2004 and 2014 tourism products were income elastic during slow growth periods (luxurious) and income inelastic (necessities) during fast growthperiods. The reasons for the changing income elasticity of the tourism demand across the business cycle are loss aversion, liquidity constraints, and precautionary savings (Smeral, 2016).…”
Section: Changes In Income/tourism Demand Relationshipmentioning
confidence: 99%